My peolple the history of those Christians sometimes called Plymouth Brethren - Baylis, Robert H. 1924- (Wheaton, IL Harold Shaw, 1997)
Includes bibliographical references and index.
Keywords: Brethren movement -- history; Brethren movement -- doctrines